UNDERSTANDING MELATONIN : HEALTH BENEFITS AND EFFECTS - Pimsarn, Nopphadol; limlikidaksorn, Chavalit; Buachsantia, Narathip (Journal of MCU Nakhondhat, 2023)
The purpose of this article is to examine the efficacy of melatonin in the treatment or resolution of insomnia. By using the method of reviewing literature from national and international academic databases. The results of the literature review showed that melatonin is a hormone involved in the regulation of sleep-in humans. Oral melatonin has proven effective in the treatment of insomnia and the improvement of sleep efficiency in children and adolescents, young adults and the elderly. To date, no serious adverse effects linked to melatonin use have been reported. Most research has found that melatonin appears to be harmless if taken for short periods of time or intermittently. However, one of the limitations of melatonin research is the lack of monitoring and evaluation of melatonin intake. So it is not possible to conclude that melatonin is harmless. In foreign countries, melatonin products are distributed in a dietary supplement format. In Thailand, however, melatonin is classed as a medicine. It is regulated by the Drugs Act and other drug-related statutes. This should only be prescribed by a physician within a medical setting. Hence, taking melatonin to treat insomnia Consequently, it should be under the close supervision of a physician. And should not purchase melatonin products to eat on their own because there can be adverse effects on the body. In addition, relevant organizations should accelerate public education and awareness of melatonin limits because there are so many melatonin supplements sold online.